2013
DOI: 10.7897/2230-8407.04530
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Comorbidities and Life Style Associated With Diabetes Patients

Abstract: The present study focused on the co morbidities and lifestyle associated with diabetes patients. It was a non experimental prospective study and done in outpatient department of endocrinology, Amrita Institute of Medical science. Sample size was 136. Patients who have diagnosed with diabetes included and not willing to participate excluded. Majority of the people (18.4%) having hypertension followed by combination of hypertension and dyslipidaemia (15.4%). Majority of them are non vegetarians (79.41%) and havi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…More than half of the patients had obesity, hypertension, and hypercholesterolemia. Several other studies also showed that these three diseases are the common comorbid conditions of diabetics 11,18,19,28,29 .…”
Section: Discussionmentioning
confidence: 88%
“…More than half of the patients had obesity, hypertension, and hypercholesterolemia. Several other studies also showed that these three diseases are the common comorbid conditions of diabetics 11,18,19,28,29 .…”
Section: Discussionmentioning
confidence: 88%
“…are again area of reconsideration of therapy for longer duration .Epidemiological studies revealed that a distinct group of disease is quite frequently associated with psoriasis. 2 Due to the chronic and relapsing nature of the disease large number of patients are seeking treatment from ayurveda and other traditional system of medicine. Ayurveda through its holistic approach particularly by samshodhana chikitsa which aims at correcting the basic causative factor is the first line of treatment advised for all skin diseases(Kushtha).…”
Section: Introductionmentioning
confidence: 99%